Optimization of Wi-Fi Network Performance Using Simple Queue and Filter Rules Mikrotik - Salwa Saumi; Indra Saputra; Jordy Lasmana Putra (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
The development of information technology requires stable internet access for corporate operations. The company Primantara Cendana Sakti, a printing service provider, experienced obstacles such as connection lag and significant speed drops due to uneven bandwidth distribution among users. This research aims to optimize network performance by designing a configuration using a MikroTik router. The study employs a virtual network development model consisting of analysis, design, and configuration phases. The proposed solution implements the Simple Queue method for equitable bandwidth allocation and Firewall Filter Rules to restrict non-productive traffic. Results indicate that the implementation successfully eliminates connection monopolies, ensuring each personal computer receives a stable allocation of two Megabits per second for downloads and one Megabit per second for uploads. Furthermore, the security layer effectively blocks high-risk traffic such as peer-to-peer packets and unauthorized video streaming. This structured approach transforms the previously unmanaged environment into a high-performance ecosystem. The system ensures that the network is performance-balanced and resilient against cyber threats. Consequently, operational efficiency and data security within the company are significantly improved. This research provides a structured guide for small and medium enterprises to optimize their wireless fidelity network infrastructure.